SMC1A regulated by KIAA1429 in m6A-independent manner promotes EMT progress in breast cancer - Xu Zhang; Xin-Yuan Dai; Jia-Yi Qian; Feng Xu; Zhang-Wei Wang; Tian Xia; Xu-Jie Zhou; Xiao-Xia Li; Liang Shi; Ji-Fu Wei; Qiang Ding (Elsevier, 2022)
As a component of N6-methyladenosine (m6A) "writers," KIAA1429 was reported to promote breast cancer proliferation and growth in m6A-independent manners. However, the related mechanism of KIAA1429 in breast cancer metastasis has not been reported. In the present study, we found KIAA1429 could significantly promote the migration and invasion of breast cancer cells. Then we demonstrated that knockdown of KIAA1429 could impede breast cancer metastasis in nude mice in vivo. The level of SNAIL expression and epithelial-mesenchymal transition (EMT) progress was positively related with KIAA1429. Furthermore, we confirmed that the suppression of cell migration, invasion, and EMT progress by knockdown of KIAA1429 could be reversed by the upregulation of SNAIL. However, structural maintenance of chromosomes 1A (SMC1A), not KIAA1429, bound with the SNAIL promoter region directly and promoted the transcription of SNAIL. Then we confirmed that KIAA1429 could bind to the motif in the 3' UTR of SMC1A mRNA directly and enhance SMC1A mRNA stability. In conclusion, our study revealed a novel mechanism of the KIAA1429/SMC1A/SNAIL axis in the regulation of metastasis of breast cancer. Moreover, it first provided detailed investigation of how KIAA1429 regulated the targeted gene expression at posttranscriptional levels as an RNA binding protein unrelated to its m6A modification.